Exploring the Mental Health Frontier: Social Media, the Metaverse and Their Impact on Psychological Well-Being - Ileana Di Pomponio; Luca Cerniglia (MDPI AG, 2024)
The emergence of social media alongside the creation of the metaverse marks two pivotal technological evolutions of our era, significantly altering the manner in which individuals engage, communicate, and understand their environment and relationships [...]